Hard X-ray Photoelectron Spectroscopy (HAXPES) - Woicik, Joseph (Springer Series in Surface Sciences, 2016)
This book provides the first complete and up-to-date summary of the state of the art in HAXPES and motivates readers to harness its powerful capabilities in their own research. The chapters are written by experts. They include historical work, modern instrumentation, theory and applications. This book spans from physics to chemistry and materials science and engineering. In consideration of the rapid development of the technique, several chapters include highlights illustrating future opportunities as well.